Examining the relationship between midwives’ attitudes toward artificial intelligence use and their job satisfaction - Nazli Unlu Bidik; Zekiye Turan (BMC Nursing)
Abstract Background Adapting to artificial intelligence technology, which has been very popular recently, is becoming inevitable for healthcare professionals. The use of technology has the potential to affect health professionals’ feelings of satisfaction towards their work. The aim of this study is to examine the relationship between midwives’ attitudes towards the use of artificial intelligence and their job satisfaction. Metods This descriptive study was conducted with 804 midwives between June and November 2024. The study data were collected with the Demographic Information Form, the Health Professionals’ Attitudes Towards The Use of Artificial Intelligence Scale and Minnesota Job Satisfaction Scale. Descriptive statistics including percentages and averages were used to analyze the data. Independent sample t-tests were used to compare two groups, one-way analysis of variance (ANOVA) was used to compare more than two groups, and Pearson correlation analysis was used to examine the relationship between two continuous variables. Results The mean age of the midwives participating in the study was 32.58 ± 8.39 years. There is a statistically significant difference between the status of midwives’ receiving artificial intelligence training and using artificial intelligence tools and their midwives’ attitudes towards the use of artificial intelligence scores (t = 4.795, p = 0.001; t = 3.877, p = 0.001). There is a statistically significant difference between the status of midwives’ receiving artificial intelligence training and using artificial intelligence tools and their job satisfaction scores (t = 2.305, p = 0.029; t = 3.289, p = 0.001). A low level significant relationship was found between midwives’ job satisfaction levels and their attitudes towards the use of artificial intelligence (r = 0.109, p = 0.002). Conclusion Determining the artificial intelligence attitudes of midwives is valuable for the development of artificial intelligence supported systems and the integration of these systems into the field. As midwives’ attitudes towards the use of artificial intelligence increase positively, their job satisfaction levels increase. Expanding the use of artificial intelligence tools will increase job satisfaction and improve the quality of health care. The implication for nursing and midwifery management In order to increase the quality of health care, midwives’ job satisfaction should be increased. For this, first of all, midwives’ adaptation to the developing technology and their attitudes towards it should be determined. In order to integrate artificial intelligence, which is the latest technology, into the field of health and to eliminate concerns, it is necessary to provide trainings on this subject and to increase positive attitudes. The widespread use of artificial intelligence will be effective in increasing the job satisfaction of midwives.